Exploring Junior High School Students’ External Representations in Solving Solid Geometry Problems: A Descriptive Qualitative Study - Fadhia Aliva Wibowo; Rohati Rohati; Duano Sapta Nusantara (Journal of General Education and Humanities, 2025)
External representation is essential in mathematics learning because it enables students to express and operationalize abstract ideas. However, many junior high school students still struggle to coordinate visual, mathematical, and verbal representations when solving solid geometry problems. This study aims to explore how students demonstrate external representations in solving solid geometry tasks by analyzing their pretest responses. A descriptive qualitative method was used involving nine students who completed a pretest, from which three were purposively selected to represent high, medium, and low levels of external representation ability. Data were collected using a test instrument based on indicators of visual, mathematical, and verbal representations. The results show that high-performing students can consistently produce accurate visualizations, mathematical expressions, and written explanations, while medium-performing students demonstrate inconsistent and partial representations. Low-performing students encounter major difficulties in generating meaningful representations. The findings suggest that teachers should strengthen geometry instruction by promoting the balanced use of visual, mathematical, and verbal representations to support students’ conceptual understanding.